018 Cold mountain: do delays to hospital increase the risk of hypothermia in mountain casualties?. Issue 3 (1st March 2011) - Jones, Benjamin; Dykes, Linda
Abstract : Introduction: UK mountain casualties are at risk of hypothermia year-round. Mountain Rescue personnel are often taught that pre-hospital treatment of hypothermia cannot reverse cooling of casualties and so delays in evacuation increase the severity of hypothermia on arrival to hospital. We wondered if this was true—our ED receives many mountain casualties, but very few arrive genuinely hypothermic. Aim: To determine the relationship between hypothermia and delay on reaching hospital in mountain casualties in Snowdonia. Method: We interrogated the Mountain Medicine database of casualties brought to our ED following assistance from Mountain Rescue services. We noted temperature on arrival, and delay in reaching hospital (defined as activation time of mountain rescue to arrival of casualty in the ED). Results: 402 mountain casualties attended our ED over a 5-year period Jan 2004–Dec 2008. 152/402 had temperature recorded on arrival in ED. 20/152 were truly hypothermic (<35°C) on arrival. A further 97/152 had a temperature of 35°C–36.9°C on arrival. Mean delay in evacuation to hospital was 118.3 min (Range 12–380 min, median 121.5, mode 144). There was a positive correlation between shorter transit times and lower recorded temperatures on arrival: R 2 =0.0635 for genuinely hypothermic (<35°C) patients; R 2 =0.0495 for all patients <37°C. Discussion: This data does not support the assumption that casualties inexorably lose heat whilst awaiting evacuation to hospital: casualties who spent longest on the mountainside were warmer than those with short evacuation times. Strategies used by mountain rescue services may be effective in preventing (possibly reversing) heat loss. However it's also possible that sick/injured casualties who are already very cold might be more likely to be evacuated by helicopter, thus reducing transit time to hospital. This preliminary, retrospective data deserves validation with a prospective study ideally with temperatures measured as rescuers arrive on-scene.